“TENDING A BOND TO ENSLAVE THEM”: EVANGELIZATION IN THE PROVINCE OF DARIEN, EIGHTEENTH CENTURY - Vásquez Pino, Daniela (2017)
The evangelization in America during the Vice Royal Era, illustrated in the establishment of frontier missions, attempted to transform its inhabitants “barbarians” into faithful vassals to the Crown. This article analyzes the complexity of the missionary presence in the Darien and the relationships that were woven between the cunas and the Spanish officials (especially missionaries, soldiers, and landowners). These relations are related to mistreatment of the cunas, the fears of the settlers of an indigenous rebellion, and the need for Spanish permanence in the Darien territory, which is so important for the transatlantic geopolitics of the eighteenth century.